Sudan State-Level Public Expenditure Review : Meeting the Challenges of Poverty Reduction and Basic Service Delivery, Synthesis Report - World Bank (World Bank, Washington, DC, 2015)
Sudan has the potential to become a dynamic economy and a bread basket for the Arab world and East-Central Africa. However, resource endowment is not sufficient to bring about sustainable growth and prosperity. Sudans macroeconomic conditions remain weak since the secession of South Sudan in 2011, despite some improvements. The repercussions of the secession of South Sudan present enormous challenges for Sudan with respect to managing the macro-fiscal adjustment and promoting a structural re-orientation of the economy. The signing in March 2013 of the implementation matrix of the agreement between Sudan and South Sudan provides some fresh financial relief to Sudan and creates a great opportunity for further policy reforms to address the post-secession challenges. Sudans growth strategy should involve policies aimed at improving the investment climate and broadening private sector-led growth, and diversifying the economy toward non-oil sectors such as agriculture, industry, export, and local trade.